Partnership, empowerment and local development - VASCONCELLOS SOBRINHO, Mário (2015)
This paper tries to understand how partnership between local organisations (associations, cooperatives, worker's unions and others) and Government affects local development. It explores to what extent partnership is an effective strategy for local development in areas of historical conflict between local Government and the local organisations that defend the interests of family-based, small-scale rural producers. Particularly, this paper concentrates on debate of partnership as a mechanism of power sharing and empowerment of the people that historically have been excluded from the development process. Empirically, the paper is based on data collected in the municípios of Ourém and Igarapé-Miri, Northeast of Para State, Amazonia, Brazil.